An Alchemical Exposition of “The Rime of the Ancient Mariner” - Zahid Ali Shah, Syed (The Journal of Humanities & Social Sciences, 2022)
In its essence, alchemy strives to arrive at a harmonious synthesis of the contending opposites. The maxim “Dissolve and coagulate” encompasses in its precision not only Jung’s extensive alchemical deliberations but also Coleridge’s theoretical formulations on “Imagination.” A conceptual belief in life’s struggle towards unification and coherence is seen in Jung and Coleridge both as the outcome of an intense struggle of conflicting and contending mental and psychological processes in the background. The chaos of contending tendencies, followed by an analysis in isolation of these opposing forces, and a final resolution into harmony is what alchemy proceeds with. This paper is an analysis of how these opposing and conflicting tendencies, psychologically and alchemically, are resulting in a wholeness through the symbolic cluster of “The Rime of the Ancient Mariner”.